Study the Influence of Captopril on Bone Metabolism in Elderly Hypertensive Women - Zahraa A. Mousa; Nada N. Al-Shawi; Ahmed A. Omar (College of Pharmacy University of Baghdad, 2017)
Widespread use of antihypertensive agents in clinical practice necessitates the knowledge of their pleiotropic effects. At the present time there are no sufficient evidences of positive effect of these medications on bone coming from randomized controlled trials; knowledge of additional effects of those drugs on the bone metabolism will allow doctors to choose optimal treatment of hypertension, taking into account the state of bone tissue. At the same time it will also allow to prevent osteoporosis in patients having osteoporosis risk factors or initial signs of bone loss. Ten elderly hypertensive women age > 60 years old (64.2Â±3.6) treated with captopril for a 5-6 years ago while they attending Al Yarmouk Teaching Hospital in Baghdad; in addition, newly-diagnosed hypertensives, and normotensive of the aged-matched women were participated in this study that were conducted during the period (January- May 2014). Measurement of serum calcium, magnesium, inorganic phosphorus, total alkaline phosphatase activity, and parathyroid hormone were done, in addition to spine mineral density and t-score of such bone density by dual energy x-ray absorptiometry. The results of this study showed that there were no significant differences in the serum levels of calcium, magnesium, inorganic phosphorus, total alkaline phosphatase activity, and parathyroid hormone in postmenopausal hypertensive women treated for 5-6 years with captopril compared to newly-diagnosed and to aged-matched normotensive women. In addition, non-significant differences were observed in the level of bone mineral density and t score of bone mineral density in all groups of the study. In conclusion, the present study provides additional knowledge concerning the influence of captopril treatment on some selected parameters of bone metabolism in elderly hypertensive women. Keywords: Captopril, Bone metabolism, Elderly women, Hypertension, Dual energy x-ray absorptiometry.